Resource Allocation in Multicore Elastic Optical Networks: A Deep Reinforcement Learning Approach - Juan Pinto-Ríos; Felipe Calderón; Ariel Leiva; Gabriel Hermosilla; Alejandra Beghelli; Danilo Bórquez-Paredes; Astrid Lozada; Nicolás Jara; Ricardo Olivares; Gabriel Saavedra (Complexity)
A deep reinforcement learning (DRL) approach is applied, for the first time, to solve the routing, modulation, spectrum, and core allocation (RMSCA) problem in dynamic multicore fiber elastic optical networks (MCF-EONs). To do so, a new environment was designed and implemented to emulate the operation of MCF-EONs - taking into account the modulation format-dependent reach and intercore crosstalk (XT) - and four DRL agents were trained to solve the RMSCA problem. The blocking performance of the trained agents was compared through simulation to 3 baselines RMSCA heuristics. Results obtained for the NSFNet and COST239 network topologies under different traffic loads show that the best-performing agent achieves, on average, up to a four-times decrease in blocking probability with respect to the best-performing baseline heuristic method.